Effect of an integrated neonatal care kit on cause-specific neonatal mortality in rural Pakistan - Jessica Duby; Lisa G. Pell; Shabina Ariff; Amira Khan; Afsah Bhutta; Daniel S. Farrar; Diego G. Bassani; Masawar Hussain; Zulfiqar A. Bhutta; Sajid Soofi; Shaun K. Morris (Taylor & Francis Group, 2020)
Background In 2018, Pakistan had the world's highest neonatal mortality rate. Within Pakistan, most neonatal deaths occur in rural areas where access to health facilities is limited, and robust vital registration systems are lacking. To improve newborn survival, there is a need to better understand the causes of neonatal death in high burden settings and engage caregivers in the promotion of newborn health. Objective To describe the causes of neonatal death in a rural area in Pakistan and to estimate the effect of an integrated neonatal care kit (iNCK) on cause-specific neonatal mortality. Methods We analyzed data from a community-based, cluster-randomized controlled trial of 5286 neonates in Rahim Yar Khan (RYK), Punjab, Pakistan between April 2014 and August 2015. In intervention clusters, Lady Health Workers (LHW) delivered the iNCK and education on its use to pregnant women while control clusters received the local standard of care. The iNCK included interventions to prevent and identify signs of infection, identify low birthweight (LBW), and identify and manage hypothermia. Verbal autopsies were attempted for all deaths. The primary outcome was cause-specific neonatal mortality. Results Verbal autopsies were conducted for 84 (57%) of the 147 reported neonatal deaths. The leading causes of death were infection (44%), intrapartum-related complications (26%) and prematurity/LBW (20%). There were no significant differences in neonatal mortality due to prematurity/LBW (RR 0.43; 95% CI 0.15-1.24), infection (RR 1.10; 95% CI 0.58-2.10) or intrapartum-related complications (RR 1.04; 95% CI 0.0.45-2.41) among neonates who died in the intervention arm compared to those who died in the control arm. Conclusion The major causes of neonatal deaths in RYK, Pakistan mirror the global landscape of neonatal deaths. The iNCK did not significantly reduce any cause-specific neonatal mortality.